Analisis Kebijakan Dividen Perusahaan Manufaktur Di Indonesia : Berdasarkan Penerapan Signaling Theory - Salsabila Arianto; Nur Ikhlasul Amal; Muh. Rizaldi; Linda Arisanty Razak; Amril Amril (Jurnal Riset Akuntansi Politala, 2026)
This study aims to examine the application of signaling theory to the dividend policy of manufacturing companies in Indonesia, analyze the role of dividend policy as a signal regarding the company's performance prospects, and identify factors that strengthen the effectiveness of this dividend signal. The research method used is a Systematic Literature Review (SLR) by examining relevant empirical articles published in the 2020–2025 period, obtained from reputable academic databases. The results of the study indicate that dividend policy in manufacturing companies in Indonesia generally functions as a positive signal regarding the company's performance prospects, especially when supported by high profitability, large company size, efficient asset utilization, and consistent dividend payments. However, the effectiveness of dividend signals is contextual and can weaken companies with high levels of leverage and free cash flow. Overall, the findings of this study confirm that dividend policy plays a role not only as a profit distribution mechanism but also as a strategic tool in reducing information asymmetry and increasing investor confidence in the long-term prospects of manufacturing companies in Indonesia.